Engineering of two-dimensional materials for energy storage and conversion - Koh, See Wee (Nanyang Technological University, 2022)
Negative impacts of reliance on fossil fuel on both environment and economy are becoming more apparent and urgent. This calls for a severe paradigm shift and serious actions toward sustainable energy supply chain. Developing clean and green energy especially from non-carbon generating sources is a crucial step in the direction. To this end, renewable energies such as solar and wind energy are perfect solutions. Energy conversion devices such as solar cell and wind turbine can convert these natural energy forms to electricity. Nevertheless, renewable energies are intermittent, which necessitates energy storage devices such as batteries that store the renewable electricity in terms of chemical energy. However, this chemical energy storage is not stable and self-discharge of batteries is inevitable. A more stable energy storage is to store renewable electricity in the form of chemical fuels. For instance, solar-to-hydrogen conversion effectively stores solar energy in stable hydrogen chemical bonds, which are stable for centuries. A key component of these energy conversion and storage device is catalyst, particularly hydrogen and oxygen reaction catalysts. For instance, hydrogen and oxygen evolution catalysts play critical roles in water electrolysis for green hydrogen generation. Oxygen reduction reaction (ORR) catalyst is widely employed in metal-oxygen batteries, a high-capacity energy storage device. An ideal catalyst should have high activity and stability, low cost, and great abundance. The high activity is often achieved by high intrinsic activity of active sites, and high density of these active sites (per unit geometric area), which needs high surface area. High surface area also improves utilization rate of the catalyst materials, which is very crucial for reducing the cost of precious metal catalysts. The high activity also strongly depends on the electrical conductivity of the catalyst. To this end, two-dimensional materials (2DMs) has gained traction for catalysing energy conversion and storage due to their high specific surface area, excellent mechanical properties, great electrical and thermal conductivity. The most alluring feature of 2DMs is their ability to be modified to exhibit different functions. In this thesis, 2DMs are modified to improve their applicability in energy applications, especially for oxygen reduction reaction and solar energy conversion/storage. I will present a showcase of how lithiation activation technique for PdSe2 can balance the stability and performance of the material for ORR catalysis. Moreover, an unprecedented palladium phosphoronitride-based ORR catalyst is produced by a simple annealing of Pd3P2S8. Lastly, I will present the functionalisation of MXene that can tune the work function in a wide range, which could find wide application in optoelectronic devices, e.g., solar cell. Additionally, the functionalisation of a new class of 2DM, MXene, had achieved highly efficient solar light to heat conversion for water desalination.